2007
DOI: 10.1002/ijc.22467
|View full text |Cite
|
Sign up to set email alerts
|

Rose bengal staining in detection of oral precancerous and malignant lesions with colorimetric evaluation: A pilot study

Abstract: Early detection of oral precancerous and malignant lesions is still a diagnostic challenge for most of clinicians, and ideal adjuncts for detection of these lesions are currently unavailable. Our preliminary study has indicated that rose bengal (RB) staining might have the potency as a diagnostic aid; however, its clinical significance and reliability in hospital-based population are still not clear. In the present study, we investigated the efficacy of RB staining in detection of oral precancerous and maligna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(19 citation statements)
references
References 31 publications
(27 reference statements)
0
18
0
1
Order By: Relevance
“…The authors concluded that RB staining can be used as a valuable diagnostic procedure in hospital-based population (with a high prevalence of malignancy dysplasia). Further research is necessary to reveal its benefits as a screening test (Du et al 2007). …”
Section: Other Staining Methodsmentioning
confidence: 99%
“…The authors concluded that RB staining can be used as a valuable diagnostic procedure in hospital-based population (with a high prevalence of malignancy dysplasia). Further research is necessary to reveal its benefits as a screening test (Du et al 2007). …”
Section: Other Staining Methodsmentioning
confidence: 99%
“…Du et al 22 conducted a study in which six lesions with normal clinical appearance were stained by Rose Bengal staining. So, the authors concluded that it can be used as a diagnostic procedure, but further research is required.…”
Section: 21mentioning
confidence: 99%
“…Two studies demonstrated that RB staining may be a valuable diagnostic technique in the detection of oral PMDs and oral cancer (Du et al 2007;Mittal et al 2012). In one study, authors investigated the efficacy of RB staining in the detection of oral PMDs and (Warnakulasuriya and Johnson 1996;Epstein et al 1997;Ram and Siar 2005;Epstein et al 2008;Lingen et al 2008;Patton et al 2008;Balevi 2011;Awan et al 2012;Mojsa et al 2012;Rajmohan et al 2012) Methylene blue staining 90-91.4 66.6-69 (Chen et al 2007a;Chen et al 2007b;Riaz et al 2013) Rose bengal staining 90-100 73.7-89.09 (Du et al 2007;Zhang et al 2013) Lugol's iodine staining 87.5-94.7 83.8-84.2 (Epstein et al 1992;Chaudhari et al 2013) Light-based detection systems…”
Section: Rose Bengal Stainingmentioning
confidence: 99%
“…Raman spectroscopy 97.44-100 77-100 (Li et al 2010;Guze et al 2015) Elastic scattering spectroscopy 72-98 68-75 (Jerjes et al 2004;Sharwani et al 2006b;Green et al 2014) Diffuse reflectance spectroscopy 76-100 76-97 (Mallia et al 2010;Jayanthi et al 2011;Stephen et al 2013) Narrow-band imaging 84.62-96 88.2-100 (Piazza et al 2010;Yang et al 2012b;Yang et al 2013;Shibahara et al 2014;Vu and Farah 2014;Yang et al 2014) Optical coherence tomography 73-100 78-98 (Matheny et al 2004;Wilder-Smith et al 2004;WilderSmith et al 2005;Wilder-Smith et al 2009;Olivo et al 2011;Hamdoon et al 2013;Green et al 2014) Confocal laser endomicroscopy 80 100 (Nathan et al 2014) Confocal reflectance microscopy 73 88 (Olivo et al 2011) Salivary biomarker miRNA-184 n/a n/a (Zahran et al 2015) IL-6 n/a n/a (Sharma et al 2011) oral cancer in 132 patients, and concluded that RB staining seemed promising for the detection of epithelial dysplasia in oral leukoplakia, lichen planus, and leukokeratosis (Du et al 2007). Zhang et al (2013) combined fluorescence spectroscopic techniques with RB staining to detect oral PMDs in an animal model in vivo and reported that the method showed excellent sensitivity.…”
Section: Chemiluminescencementioning
confidence: 99%